2021
DOI: 10.3390/jcm10071539
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and the Risk of COVID-19 Infection and Mortality: A Nationwide Population-Based Case-Control Study

Abstract: Regular physical activity (PA) is known to reduce the risk of serious community-acquired infections. We examined the association of PA with the morbidity and mortality resulting from coronavirus disease (COVID-19) infection in the South Korean population. Patients who tested positive for severe acute respiratory coronavirus 2 and who underwent public health screening between 2014 and 2017 (n = 6288) were included. Age- and sex-matched controls (n = 125,772) were randomly selected from the Korean National Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 29 publications
1
55
0
4
Order By: Relevance
“…All patients were followed up until 4 months after the diagnosis of COVID-19 or until death. A more detailed protocol has been previously published [ 17 ]. We presented the STORBE checklist in Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…All patients were followed up until 4 months after the diagnosis of COVID-19 or until death. A more detailed protocol has been previously published [ 17 ]. We presented the STORBE checklist in Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…A higher percentage (50%) of the decrease of the risk of hospitalization in case of SARS-CoV-2 infection was found by Sallis et al (2021) - [20] , the association being valid for a moderate to strenuous effort intensity and for physical activity performed by the patient in the last 2 years before illness [20] . For the same intensity of effort (established by a questionnaire method in patients infected with the virus), Korean researchers found a 10% decrease in the risk of infection and a 53% decrease in mortality, independent of confounding factors [21] . The online completion of a questionnaire about the level of physical activity and severity of COVID-19 by participants previously infected with SARS-CoV-2 revealed that the possibility of hospitalization decreases by 64% in those able to maintain a brisk walk (thus moderate effort) [22] .…”
Section: Validation Of Hypothesismentioning
confidence: 96%
“…Yet, there is no upper limit on the intensity of effort for exercises used to prevent severe forms of COVID-19. There may be a temptation to increase the body's stress, given that a standard deviation increment in MET/week (525.3 MET-min/week) was associated with a 4% decrease in the risk of COVID-19 morbidity [21] .…”
Section: Implications Of the Hypothesismentioning
confidence: 99%
“…The higher the physical activity and the better the cardiopulmonary function, the lower the possibility of infection with COVID-19 and the lower the mortality rate [4]. Therefore, the importance of regular physical activity and exercise programs for improving physical fitness based on sport science and Kinesiology is being emphasized.…”
Section: Editorialmentioning
confidence: 99%